Answer

Verified

454.2k+ views

Hint- Here, we will be using Pythagoras theorem and will be converting all other sides in terms of sides AD and AB which are present in the equation which needs to be proved.

To prove- $9{\left( {{\text{AD}}} \right)^2} = 7{\left( {{\text{AB}}} \right)^2}$

Let us draw an equilateral $\vartriangle {\text{ABC}}$ with sides AB, BC and AC equal to each other. Also, draw a line from the vertex A which will meet the side BC at point D such that ${\text{BD}} = \dfrac{1}{3}\left( {{\text{BC}}} \right)$. Also, draw a perpendicular from the vertex A on the side BC which divides line BC into two equal parts i.e., ${\text{BE}} = {\text{CE}} = \dfrac{{{\text{BC}}}}{2}$

As, ${\text{BD}} = \dfrac{1}{3}\left( {{\text{BC}}} \right){\text{ }} \to {\text{(1)}}$

Here, ${\text{AB}} = {\text{BC}} = {\text{AC}}$ and ${\text{DE}} = \left( {{\text{BE}} - {\text{BD}}} \right)$

As we know that, Pythagoras theorem states that the square of the hypotenuse is equal to the sum of the squares of perpendicular and base in a right angled triangle.

In right angled $\vartriangle {\text{ADE}}$,

Using Pythagoras theorem \[{\left( {{\text{AD}}} \right)^2} = {\left( {{\text{AE}}} \right)^2} + {\left( {{\text{DE}}} \right)^2} \Rightarrow {\left( {{\text{AD}}} \right)^2} = {\left( {{\text{AE}}} \right)^2} + {\left( {{\text{BE}} - {\text{BD}}} \right)^2}{\text{ }} \to {\text{(2)}}\]

In right angled $\vartriangle {\text{ABE}}$,

Using Pythagoras theorem \[{\left( {{\text{AB}}} \right)^2} = {\left( {{\text{AE}}} \right)^2} + {\left( {{\text{BE}}} \right)^2} \Rightarrow {\left( {{\text{AE}}} \right)^2} = {\left( {{\text{AB}}} \right)^2} - {\left( {{\text{BE}}} \right)^2} \Rightarrow {\left( {{\text{AE}}} \right)^2} = {\left( {{\text{AB}}} \right)^2} - {\left( {\dfrac{{{\text{BC}}}}{2}} \right)^2}{\text{ }} \to {\text{(3)}}\]

Now using equation (3) in equation (2), we get

\[ \Rightarrow {\left( {{\text{AD}}} \right)^2} = {\left( {{\text{AB}}} \right)^2} - {\left( {\dfrac{{{\text{BC}}}}{2}} \right)^2} + {\left( {{\text{BE}} - {\text{BD}}} \right)^2}{\text{ }}\]

Using ${\text{BE}} = \dfrac{{{\text{BC}}}}{2}$ and ${\text{BD}} = \dfrac{1}{3}\left( {{\text{BC}}} \right)$ , the above equation becomes

\[

\Rightarrow {\left( {{\text{AD}}} \right)^2} = {\left( {{\text{AB}}} \right)^2} - {\left( {\dfrac{{{\text{BC}}}}{2}} \right)^2} + {\left( {\dfrac{{{\text{BC}}}}{2} - \dfrac{{{\text{BC}}}}{3}} \right)^2} = {\left( {{\text{AB}}} \right)^2} - \left[ {\dfrac{{{{\left( {{\text{BC}}} \right)}^2}}}{4}} \right] + {\left( {\dfrac{{{\text{3BC}} - {\text{2BC}}}}{6}} \right)^2} = {\left( {{\text{AB}}} \right)^2} - \left[ {\dfrac{{{{\left( {{\text{BC}}} \right)}^2}}}{4}} \right] + \left[ {\dfrac{{{{\left( {{\text{BC}}} \right)}^2}}}{{36}}} \right] \\

\Rightarrow {\left( {{\text{AD}}} \right)^2} = {\left( {{\text{AB}}} \right)^2} + \left[ {\dfrac{{{{\left( {{\text{BC}}} \right)}^2}}}{{36}} - \dfrac{{{{\left( {{\text{BC}}} \right)}^2}}}{4}} \right] = {\left( {{\text{AB}}} \right)^2} + \left[ {\dfrac{{{{\left( {{\text{BC}}} \right)}^2} - 9{{\left( {{\text{BC}}} \right)}^2}}}{{36}}} \right] = {\left( {{\text{AB}}} \right)^2} + \left[ {\dfrac{{ - 8{{\left( {{\text{BC}}} \right)}^2}}}{{36}}} \right] = {\left( {{\text{AB}}} \right)^2} - \left[ {\dfrac{{2{{\left( {{\text{BC}}} \right)}^2}}}{9}} \right] \\

\]

Also, ${\text{AB}} = {\text{BC}} = {\text{AC}} \Rightarrow {\text{BC}} = {\text{AB}}$so the above equation becomes

\[

\Rightarrow {\left( {{\text{AD}}} \right)^2} = {\left( {{\text{AB}}} \right)^2} - \left[ {\dfrac{{2{{\left( {{\text{BC}}} \right)}^2}}}{9}} \right] = {\left( {{\text{AB}}} \right)^2} - \dfrac{{2{{\left( {{\text{AB}}} \right)}^2}}}{9} = \dfrac{{9{{\left( {{\text{AB}}} \right)}^2} - 2{{\left( {{\text{AB}}} \right)}^2}}}{9} = \dfrac{{7{{\left( {{\text{AB}}} \right)}^2}}}{9} \\

\Rightarrow 9{\left( {{\text{AD}}} \right)^2} = 7{\left( {{\text{AB}}} \right)^2} \\

\]

The above equation is the equation we needed to prove. Hence it is proved.

Note- In any right angled triangle, the side opposite to the right angle is known as hypotenuse. In this particular problem in order to obtain the LHS of the equation which needs to be proved, Pythagoras theorem is applied in the right triangle ADE and then all the other sides except AD are converted in terms of side A

To prove- $9{\left( {{\text{AD}}} \right)^2} = 7{\left( {{\text{AB}}} \right)^2}$

Let us draw an equilateral $\vartriangle {\text{ABC}}$ with sides AB, BC and AC equal to each other. Also, draw a line from the vertex A which will meet the side BC at point D such that ${\text{BD}} = \dfrac{1}{3}\left( {{\text{BC}}} \right)$. Also, draw a perpendicular from the vertex A on the side BC which divides line BC into two equal parts i.e., ${\text{BE}} = {\text{CE}} = \dfrac{{{\text{BC}}}}{2}$

As, ${\text{BD}} = \dfrac{1}{3}\left( {{\text{BC}}} \right){\text{ }} \to {\text{(1)}}$

Here, ${\text{AB}} = {\text{BC}} = {\text{AC}}$ and ${\text{DE}} = \left( {{\text{BE}} - {\text{BD}}} \right)$

As we know that, Pythagoras theorem states that the square of the hypotenuse is equal to the sum of the squares of perpendicular and base in a right angled triangle.

In right angled $\vartriangle {\text{ADE}}$,

Using Pythagoras theorem \[{\left( {{\text{AD}}} \right)^2} = {\left( {{\text{AE}}} \right)^2} + {\left( {{\text{DE}}} \right)^2} \Rightarrow {\left( {{\text{AD}}} \right)^2} = {\left( {{\text{AE}}} \right)^2} + {\left( {{\text{BE}} - {\text{BD}}} \right)^2}{\text{ }} \to {\text{(2)}}\]

In right angled $\vartriangle {\text{ABE}}$,

Using Pythagoras theorem \[{\left( {{\text{AB}}} \right)^2} = {\left( {{\text{AE}}} \right)^2} + {\left( {{\text{BE}}} \right)^2} \Rightarrow {\left( {{\text{AE}}} \right)^2} = {\left( {{\text{AB}}} \right)^2} - {\left( {{\text{BE}}} \right)^2} \Rightarrow {\left( {{\text{AE}}} \right)^2} = {\left( {{\text{AB}}} \right)^2} - {\left( {\dfrac{{{\text{BC}}}}{2}} \right)^2}{\text{ }} \to {\text{(3)}}\]

Now using equation (3) in equation (2), we get

\[ \Rightarrow {\left( {{\text{AD}}} \right)^2} = {\left( {{\text{AB}}} \right)^2} - {\left( {\dfrac{{{\text{BC}}}}{2}} \right)^2} + {\left( {{\text{BE}} - {\text{BD}}} \right)^2}{\text{ }}\]

Using ${\text{BE}} = \dfrac{{{\text{BC}}}}{2}$ and ${\text{BD}} = \dfrac{1}{3}\left( {{\text{BC}}} \right)$ , the above equation becomes

\[

\Rightarrow {\left( {{\text{AD}}} \right)^2} = {\left( {{\text{AB}}} \right)^2} - {\left( {\dfrac{{{\text{BC}}}}{2}} \right)^2} + {\left( {\dfrac{{{\text{BC}}}}{2} - \dfrac{{{\text{BC}}}}{3}} \right)^2} = {\left( {{\text{AB}}} \right)^2} - \left[ {\dfrac{{{{\left( {{\text{BC}}} \right)}^2}}}{4}} \right] + {\left( {\dfrac{{{\text{3BC}} - {\text{2BC}}}}{6}} \right)^2} = {\left( {{\text{AB}}} \right)^2} - \left[ {\dfrac{{{{\left( {{\text{BC}}} \right)}^2}}}{4}} \right] + \left[ {\dfrac{{{{\left( {{\text{BC}}} \right)}^2}}}{{36}}} \right] \\

\Rightarrow {\left( {{\text{AD}}} \right)^2} = {\left( {{\text{AB}}} \right)^2} + \left[ {\dfrac{{{{\left( {{\text{BC}}} \right)}^2}}}{{36}} - \dfrac{{{{\left( {{\text{BC}}} \right)}^2}}}{4}} \right] = {\left( {{\text{AB}}} \right)^2} + \left[ {\dfrac{{{{\left( {{\text{BC}}} \right)}^2} - 9{{\left( {{\text{BC}}} \right)}^2}}}{{36}}} \right] = {\left( {{\text{AB}}} \right)^2} + \left[ {\dfrac{{ - 8{{\left( {{\text{BC}}} \right)}^2}}}{{36}}} \right] = {\left( {{\text{AB}}} \right)^2} - \left[ {\dfrac{{2{{\left( {{\text{BC}}} \right)}^2}}}{9}} \right] \\

\]

Also, ${\text{AB}} = {\text{BC}} = {\text{AC}} \Rightarrow {\text{BC}} = {\text{AB}}$so the above equation becomes

\[

\Rightarrow {\left( {{\text{AD}}} \right)^2} = {\left( {{\text{AB}}} \right)^2} - \left[ {\dfrac{{2{{\left( {{\text{BC}}} \right)}^2}}}{9}} \right] = {\left( {{\text{AB}}} \right)^2} - \dfrac{{2{{\left( {{\text{AB}}} \right)}^2}}}{9} = \dfrac{{9{{\left( {{\text{AB}}} \right)}^2} - 2{{\left( {{\text{AB}}} \right)}^2}}}{9} = \dfrac{{7{{\left( {{\text{AB}}} \right)}^2}}}{9} \\

\Rightarrow 9{\left( {{\text{AD}}} \right)^2} = 7{\left( {{\text{AB}}} \right)^2} \\

\]

The above equation is the equation we needed to prove. Hence it is proved.

Note- In any right angled triangle, the side opposite to the right angle is known as hypotenuse. In this particular problem in order to obtain the LHS of the equation which needs to be proved, Pythagoras theorem is applied in the right triangle ADE and then all the other sides except AD are converted in terms of side A

Recently Updated Pages

How many sigma and pi bonds are present in HCequiv class 11 chemistry CBSE

Why Are Noble Gases NonReactive class 11 chemistry CBSE

Let X and Y be the sets of all positive divisors of class 11 maths CBSE

Let x and y be 2 real numbers which satisfy the equations class 11 maths CBSE

Let x 4log 2sqrt 9k 1 + 7 and y dfrac132log 2sqrt5 class 11 maths CBSE

Let x22ax+b20 and x22bx+a20 be two equations Then the class 11 maths CBSE

Trending doubts

Which are the Top 10 Largest Countries of the World?

Fill the blanks with the suitable prepositions 1 The class 9 english CBSE

Difference between Prokaryotic cell and Eukaryotic class 11 biology CBSE

Difference Between Plant Cell and Animal Cell

Give 10 examples for herbs , shrubs , climbers , creepers

Change the following sentences into negative and interrogative class 10 english CBSE

Differentiate between homogeneous and heterogeneous class 12 chemistry CBSE

The Equation xxx + 2 is Satisfied when x is Equal to Class 10 Maths

Fill the blanks with proper collective nouns 1 A of class 10 english CBSE